Effective English Learning Management to Enhance Speaking Skills: A Case Study at MTs Nurul Jalal and MTs Khairul Ummah, North Jakarta - Supendi, Supendi; Abdurrahman, Nana Herdiana; Sauri, Supyan; Soro, Suharyanto H (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
This research is motivated by English language learning, especially at the Madrasah Tsanawiyah (MTs) level, which has not been effective in improving students' speaking skills. Various factors, such as the use of inappropriate learning methods, lack of facilities, and lack of student motivation, cause this. English language learning is an important aspect of education, especially in the era of globalization, which demands international communication skills. This study aims to analyze English learning management in improving students' speaking skills at MTs Nurul Jalal and MTs Khairul Ummah North Jakarta. This research is based on the philosophy of constructivism, which emphasizes the importance of the role of students in constructing knowledge through direct experience, as well as education management theory, which involves the processes of planning, organizing, implementing, and evaluating. The research method used is a qualitative case study, with data collection techniques through in-depth interviews, observation, and document analysis. Respondents consisted of teachers, principals, and students in both MTs. The results showed that learning planning in these two madrasahs is quite good. However, its implementation still requires adjustments, especially in the organization of time and the use of learning media. Obstacles faced include limited facilities such as language laboratories and students' lack of confidence in communicating using English. Nevertheless, improvement efforts such as teacher training and the use of digital technology are starting to overcome these problems. This study concludes that effective learning management, with support from all school elements, can improve students' speaking skills. There is a need for synergy between teachers, principals, and educational policies that are more supportive of the development of language competencies, especially students' speaking skills in the madrasah environment.